Why is the Correlation between Women's Labor Force Participation Rate (WLFPR) and Total Fertility Rate (TFR) Positive in Developed Countries? - Noor, Afriansyah; Widodo, Teguh; Muzakir, Muhammad Athar Ismail; ., Afifah; Konita, Ita; Asmara, Abdullah Qiqi (Journal of Ecohumanism, 2025)
This study explores the unexpected positive correlation between women's labor force participation rate (WLFPR) and total fertility rate (TFR) observed in developed countries. Using secondary data from the World Bank series (2011-2021) for the top 20 developed countries based on Human Development Index (HDI) ranking, we analyze the correlation between these two variables. The results reveal a statistically significant positive correlation between WLFPR and TFR in developed nations, suggesting that women's increased participation in the workforce is not directly associated with declining fertility rates as observed in developing countries. This finding challenges the traditional view that economic empowerment leads to lower fertility and highlights the nuanced relationship between work and family in developed contexts.